Proteome profiling of gestational diabetes mellitus at 16‐18 weeks revealed by LC‐MS/MS. Issue 9 (15th June 2020) - Liu, Xiaoting; Sun, Jingru; Wen, Xinyu; Duan, Jinyan; Xue, Dandan; Pan, Yuling; Sun, Jinghua; Zhang, Wei; Cheng, Xiaoliang; Wang, Chengbin
Abstract: Background: The practices used to diagnose gestational diabetes mellitus (GDM) could only be carried out around the time of detectable symptoms, and predictive capacity is little. Methods: LC‐MS/MS was conducted to explore overview proteomics for GDM complicated pregnant woman at 16‐18 gestation weeks, while normal pregnant for control. Enzyme‐linked immunosorbent assay was further applied in an independent cohort of 15 GDM cases and 15 controls for verification. Results: The results indicated that 24 protein expression levels were significantly changed in GDM group samples, and inflammation, oxidative stress, insulin resistance, blood coagulation, and lipid homeostasis were associated with GDM. The abnormal expression of CRP and IGFBP2 was verified in the first‐trimester maternal plasma in women who subsequently developed GDM. Conclusions: This study not only identified 24 potential predictive biomarkers for GDM also provided a global overview of protein rearrangements induced by GDM.